Eucalyptal D Enhances the Antifungal Effect of Fluconazole on Fluconazole-Resistant Candida albicans by Competitively Inhibiting Efflux Pump - Xu, Jiali; Liu, Ruihuan; Sun, Fujuan; An, Lin; Shang, Zhichun; Kong, Lingyi; Yang, Minghua (Frontiers in Cellular and Infection Microbiology, 2019)
The frequent emergence of azole-resistant strains has increasingly led azoles to fail in treating candidiasis. Combination with other drugs is a good choice to effectively reduce or retard its incidence of resistance. Natural products are a promising synergist source to assist azoles in treating resistant candidiasis. Eucalyptal D (ED), a formyl-phloroglucinol meroterpenoid, is one of the natural synergists, which could significantly enhance the anticandidal active of ﬂuconazole (FLC) in treating FLC resistant C. albicans. The checkerboard microdilution assay showed their synergistic effect. The agar disk diffusion test illustrated the key role of ED in synergy. The rhodamine 6G (R6G) efﬂux assay reflected ED could reduce drug efflux, but quantitative reverse transcription PCR analysis revealed the upregulation of CDR1 and CDR2 genes in ED treating group. Efflux pump-deficient strains were hyper-susceptible to ED, thus ED was speculated as the substrate of efflux pump Cdr1p and Cdr2p to competitively inhibit the excretion of FLC or R6G, which mainly contributed to its synergistic effect.